2020
DOI: 10.1155/2020/6450742
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glycated Proteins with Inflammatory Proteins and Periodontal Disease Parameters

Abstract: Periodontitis is a chronic inflammatory condition that may contribute to diabetogenesis. The aim was to investigate the levels of glycated proteins and their correlation with periodontal and systemic inflammation. Fifty-one patients with periodontitis and 20 healthy subjects underwent probing pocket depth (PPD) measurements. PPD total and PPD disease with and without tooth adjustment were used as continuous indices. Marginal bone loss (MBL) for mandibular premolars and molars was measured digitally. Body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…The decrease in RANKL observed in literature was attributed to immature osteoblasts and an increase in the number of osteoclasts (20). Some authors also found that serum RANKL levels were lower and OPGs were higher in diabetic patients compared to nondiabetics and prediabetics (21). The highest serum concentration of RANKL was associated with a significantly increased risk of developing type 2 diabetes (22).…”
Section: Discussionmentioning
confidence: 95%
“…The decrease in RANKL observed in literature was attributed to immature osteoblasts and an increase in the number of osteoclasts (20). Some authors also found that serum RANKL levels were lower and OPGs were higher in diabetic patients compared to nondiabetics and prediabetics (21). The highest serum concentration of RANKL was associated with a significantly increased risk of developing type 2 diabetes (22).…”
Section: Discussionmentioning
confidence: 95%
“…However, this study was conducted on a small sample ( n = 60), with adiposity being only measured with anthropometric variables, with no consideration for albumin correction. Other studies in the general population have demonstrated that serum fructosamine levels were associated negatively with fat mass [ 43 ], but no association was observed with waist circumference, fat mass, liver fat, and fat distribution [ 39 , 43 , 54 ]. Therefore, the literature generally shows contrasting results regarding the associations between fructosamine and adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Some inverse associations were also noticed between fructosamine concentrations and inflammation (adiponectin and IL-6) throughout pregnancy, without being independent of ppBMI. A cross-sectional analysis conducted in the Pakistani general population, aiming to investigate the correlations between glycated proteins and periodontal and systemic inflammation also demonstrated inverse associations, as sixteen inflammatory proteins were found to correlate inversely with fructosamine [ 39 ]. The inverse associations observed between uncorrected fructosamine and inflammatory measurements could reflect the negative associations between albumin and inflammation, as all significant correlations were lost after albumin correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fructosamine (FrAm) is another glycated AGE that has been recognized in RA [74]. Malondialdehyde (MDA) has a positive correlation with FrAm and a negative correlation with glutathione (GSH), closely associated with the formation of FrAm in RA [75].…”
Section: Vascular Complications and Autoimmune Responsementioning
confidence: 99%